Effects of various procedures for synchronisation of parturition in sows - Zaremba, W.; Udluft, T.; Bostedt, H. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2015)
Objective: The effects of various parturition controlling measures in sows on the relevant parameters for parturition were investigated. Material and methods: A total of 1975 study animals were divided into five groups: control group: A (n = 710); trial groups: B (n = 719), C (n = 180), D (n = 175), E (n = 191). The control group (A) included sows that spontaneously farrowed until day 114 of gestation. The remaining sows were administered a PGF2α-analogue (175 µg cloprostenol) on day 114. All sows that farrowed within 24 hours after prostaglandin-medication were summarised in trial group B. Dams that did not farrow until day 115 were either administered oxytocin (20 IU i. m., group C) or carbetocin in two different doses (70 µg, group D or 35 µg, group E). The sows were monitored during the peripartal period over 24 hours. Results: 83.8% of the farrowings were without any complications. The percentage of dystocia varied between the individual groups. Given a complication-free farrowing the expulsion stage began 13.0 hours (group B), 2.4 hours (group C), 1.6 hours (group D) and 1.4 hours (group E) after medication. The expulsion interval of the farrowing of two piglets decreased from 21.1 minutes with spontaneous farrowings (group A) to 18.6 minutes (group E) as a result of the administration of 35 µg carbetocin. The rate of stillborn piglets as well as the incidence of puerperal disorders and the losses of the suckling piglets also gradually, partly even significantly (p 0.05) decreased from group A to E. Conclusion and clinical relevance: The results of this study show that the use of the long-acting oxytocin carbetocin has advantages compared to oxytocin (e. g. shortened duration of birth, reduction of stillbirths). The tested dosages of carbetocin (35 µg or 70 µg) proved to be equally effective. Administration of the lower dose is recommended, since this reduces use of the active ingredient.
Keywords: Eutocia; PGF2α; oxytocin; carbetocin